2013
DOI: 10.2478/aoas-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between colour and pH in cold-stored quail breast muscle / Zależność między barwą a pH w mięśniach piersiowych przepiórek przechowywanych w warunkach chłodniczych

Abstract: The relaTionship beTween colour and ph in cold-sTored quail breasT muscle* * T a d e u s z K a r a m u c k i ♦ , J ó z e f a G a r d z i e l e w s k a , M a ł g o r z a t a J a k u b o w s k a , K i n g a R y b a k , J u s t y n a G a r c z e w s k a Faculty of Biotechnology and Animal Breeding, West Pomeranian University of Technology, Judyma 24, 71-466 Szczecin, Poland ♦ Corresponding author: tadeusz.karamucki@zut.edu.pl abstract The purpose of this study was to analyse the colour of the breast muscles of Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…According to Bocian et al [43] the meat obtained from native breed Zlotnicka Spotted pigs compared to that of hybrid pigs (PLW x PL) was characterized by a higher pHu value (P < 0.05) and lower values for drip loss (P < 0.05) and WHC (P < 0.05). Another very important area in which acidification affects meat quality is its effect on meat colour [2,9,10,20,40,44]. As an optical phenomenon, meat colour is dependent on muscle tissue structure and histological arrangement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bocian et al [43] the meat obtained from native breed Zlotnicka Spotted pigs compared to that of hybrid pigs (PLW x PL) was characterized by a higher pHu value (P < 0.05) and lower values for drip loss (P < 0.05) and WHC (P < 0.05). Another very important area in which acidification affects meat quality is its effect on meat colour [2,9,10,20,40,44]. As an optical phenomenon, meat colour is dependent on muscle tissue structure and histological arrangement.…”
Section: Discussionmentioning
confidence: 99%
“…As an optical phenomenon, meat colour is dependent on muscle tissue structure and histological arrangement. Notwithstanding the same heme pigment content, meat colour may depend on the depth of light beam penetration and its reflection or dispersion, which is predominantly observed in the variability of colour lightness measurements [22,44]. When colour was evaluated visually, the darkest meat was found in cases in which pH 45 and pH u values were high.…”
Section: Discussionmentioning
confidence: 99%
“…It depends to a large extend on the structure of the meat tissue, its acidity (pH), water holding capacity and the depth of penetration of the light beam (Lindahl et al, 2001;Karamucki et al, 2013). A darker colour L* was observed in the meat after 24 h rather than 72 h after slaughter; statistically significant changes into a lighter colour of meat were found during the storage.…”
Section: Resultsmentioning
confidence: 97%
“…The authors showed significant changes (∆) of colour in the direction of increasing its intensity (P<0.01) in the case of yellow colour b* and the hue angle h o during 48 h of the meat storage. However, Karamucki et al (2013) the highest colour changes found in the participation of red colour (∆a*) and hue angle (∆h o ) during the storage of quail muscle. In the studies of Kajak et al (2007) and Turyk et al (2013) no changes of colour parameters during the storage of meat were confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…The lightness of color L* determines the total amount of light reflected from the surface of the slice of meat [67]. It depends to a large extent on the water holding capacity, the structure of the meat tissue, its acidity (pH), and the depth of penetration of the light beam [68,69]. A study by Koch et al [53] showed that the L* value of the PL treated loin was not affected by any of the selected parameter combinations.…”
Section: Resultsmentioning
confidence: 99%